Simulations of OSPEs using socrative teacher-paced setting during the COVID-19 Pandemic / Nasibah Azme - Azme, Nasibah (Universiti Teknologi MARA, Kedah, 2020)
Due to the COVID-19 outbreak, there has been a dramatic change in education, specifically seen in the distinctive rise of the implementation of online distance learning by academic institutions. In the same way, all medical curricula have been transformed into online settings, including examinations such as the Objective Structured Practical Examinations (OSPEs), which evaluate preclinical students' practical and laboratory skills. The conventional protocol involves students being assessed at individual OSPE stations whereby a specific duration is allocated for each station. However, under the conditions mediated by the COVID-19 pandemic, there have been unprecedented challenges in generating electronic OSPEs as well as difficulties medical students face as they are undergoing online OSPEs for the first time. As it is important to ensure students are prepared for their semester exam during this pandemic, medical educators have obliged to embark on to various online platforms to generate OSPEs questions. Hence, this paper aims to provide a platform namely in the form of Socrative for the purpose of designing OSPEs questions. This platform enables educators to simulate real OSPEs by controlling the flow of questions according to set durations through the use of the teacher-paced setting. A demonstration of this process was first shown to a small group of 23 medical students, after which the Socrative teacher-paced setting was used twice. At the end of the simulation, several close-ended and open-ended questions were provided to collect respondents' feedback. The results showed that all the respondents agreed with the belief that Socrative teacher-paced setting mimics real OSPEs. Hence, this approach permits medical students to perform multiple practice attempts prior to the semester examination. Through this initiative, it is hoped that their learning and examination performance would be enhanced.